1985
DOI: 10.1080/00150198508017914
|View full text |Cite
|
Sign up to set email alerts
|

X-ray structure refinement and pyroelectric investigation of fresnoite, Ba2TiSi2O8

Abstract: 1985) X-ray structure refinement and pyroelectric investigation of fresnoite, Ba2TiSi2O8, Ferroelectrics, 62:1, 17-26, Crystal structure parameters have been refined from single crystal x-ray intensity data collected on Ba,TiSi,O, at 24 and 300°C. Anisotropic refinements in space group P4hm yielded residuals of 0.035 and 0.042 at 24 and 300°C, respectively. F'yroelectric measurements give a room temperature pyroelectric coefficient of + 10 pC m-' K-'. A structural mechanism for the pyroelectric effect is discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
41
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 20 publications
(3 reference statements)
7
41
1
Order By: Relevance
“…The bond distances and bond angles are in good agreement with the earlier report [2], although the present values are more precise. The structural refinement results given by Moore and Louisnathan [2] and Markgraf et al [9] are well matching with the present work. The single crystal data indicates that the interatomic distance Ba-O varies from 2.65 Å to 3.34 Å [9].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The bond distances and bond angles are in good agreement with the earlier report [2], although the present values are more precise. The structural refinement results given by Moore and Louisnathan [2] and Markgraf et al [9] are well matching with the present work. The single crystal data indicates that the interatomic distance Ba-O varies from 2.65 Å to 3.34 Å [9].…”
Section: Resultssupporting
confidence: 92%
“…It was reported that an elastic anomaly observed at 435 K might likely be associated with a commensurate-incommensurate phase transition [14]. However, the single crystal X-ray data taken at 297 K and at 573 K revealed no change in symmetry except small change in atomic position, the largest of which were less than 0.02 Å [9]. It has also been reported that the differential scanning calorimetry (DSC) measurement from 300 to 875 K showed a wide ($60 K) reproducible thermal anomaly at 433 K with enthalpy change DH = 60(10) J mol À1 and corresponding entropy change DS = 0.19137 J mol À1 K À1 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…That such a bonding possibiliy transforming the TiO square pyramids into highly distorted TiO octahedra that are trans-connected in this structure is not unlikely is suggested by the &&undersaturation of the bond valence in the apical oxygen'' (15). Bond valence calculations (23) using the more recent structural data on fresnoite (19) give a value of 1.368 for the apical oxygen, indeed showing considerable valence undersaturation for this oxygen. The geometric orientation of the TiO square pyramids in the structures of Cs TiOP O (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…7). Considering that fresnoite is a potential NLO structure (18,19), we believed that it is important to establish the role of square-pyramidal TiO toward SHG properties. In view of the foregoing, we prepared and examined several members of borates, silicates, and phosphates of the above-mentioned structure types containing NbO /TiO octahedral chains as well as isolated TiO square pyramids and examined their SHG response toward 1064-nm laser radiation.…”
Section: Introductionmentioning
confidence: 99%